(untitled) (Bioagro, 2020)
The use of locally available materials that meet appropriate physicochemical characteristics represents an alternative to replace commercial substrates of high cost and negative environmental impact. The objective was to characterize organic material mixtures that are available in Yucatan, Mexico, to identify their potential as substrates. Pine chips (VP) and raw sawdust (AP) were mixed with different percentages of henequen bagasse (BH) and coir dust (PC), as follows: 20BH+80AP; 30BH+70VP; 20PC+80AP; 20PC+80VP; 20PC+40AP+40VP; and 20BH+40AP+40VP. Additionally, a peat-based commercial substrate was used. Particle size, bulk density, total porosity, air-water relations, pH, electrical conductivity (CE), organic matter content, biological activity, cation exchange capacity (CEC) and the N, K+, Ca2+, Mg2+ and Na+ content was measured. All the mixtures showed high total porosity. Those containing AP+PC had particle size and water retention capacity similar to the commercial substrate, and the 20PC+80AP and 20BH+40AP+40VP mixtures surpassed it in the percentage of total available water. The 30BH+70VP mixture was superior to all the mixes in the contents of N, P, K+, and Ca2+. All the mixtures showed pH slightly higher than the recommended maximum limit (6.5), CE with values lower than 1.5 dS∙m-1, CEC with mid-levels (10 a 15 meq∙100 g-1) and low CO2 production (3.5 to 4 µmol∙m-2∙s-1) that increased in the mixtures with BH up to 9.77 µmol∙m-2∙s-1. Therefore, all mixtures have appropriate physical and chemical characteristics to consider them as alternatives for agricultural substrate.